INCIDENCE OF POST EXTRACTION COMPLICATIONS AMONG PATIENTS UNDERWENT EXTRACTIONS - AN INSTITUTIONAL BASED RETROSPECTIVE STUDY - .R, Inchara; .M, Sivakumar; . R, Subhashree (International Journal of Psychosocial Rehabilitation, 2020)
Background: A tooth extraction complication may occur like any other surgical procedure. The complications include prolonged bleeding, swelling and pain, infection, dry socket, etc. Besides, not all complications are rare. There are frequent and debilitating complications, including postoperative pain. Although the overall complications might be low and most complications are minor,. Aim: The aim of this study was to assess the post-extraction complications among patients undergoing extractions at Saveetha Dental College and hospitals from June 2019 to March 2020. Materials and methods: It is a single-centered, retrospective study with a sample size of 45 patients. The data was collected from the patient record management system used at SIMATS from June 2019 to March 2020. The data analysis was performed using SPSS software, and a chi square test was done. Results: The results of this study show that pain and swelling (36.6%) and dry socket (36.36%) are the most common post-extraction complications and mostly seen in the age group of 26-40 years (31.82%). Males (61.36%) were more prone to post-extraction complications compared to females (38.53%). Conclusion: Within the limits of the study, the common post-extraction complications include pain, swelling, and dry socket. These complications are more common in males and in patients under the age group of 20- 40 years.